New Energy Management System Based on Intelligent Digital Power Monitoring - Fakharuddin, Azhar; Nik Mohd Kamil, Nik Yusof; Muhammad, Rauf; Abdalla, Ahmed N. (2009)
Nowadays, increasing power consumption is a major cause of failure at grid due to maximum peak load and this electricity irregularity is pushing users to face troubles. This paper introduces a new Energy Management System (EMS) based on intelligent digital power monitoring. This system consists of micro controller with GSM connection to server for any decision and current transformer for monitoring of line current which is core parameter for monitoring power consumption. Our proposed algorithm will be very good solution for electrical companies to offer new electricity packages and to have a control over their user in more prominent way.